A two‐step up‐scaling method for mapping runoff and sediment production from pasture and woody encroachment on semi‐arid hillslopes. Issue 1 (22nd December 2011) - Muñoz‐Robles, Carlos; Tighe, Matthew; Reid, Nick; Frazier, Paul; Briggs, Sue V.; Wilson, Brian
ABSTRACT Management of woody encroachment and pasture to reduce runoff and sediment production is important in semi‐arid areas. However, the study of relationships between vegetation and surface hydrology at hillslope scale is difficult because of cost and time constraints. Up‐scaling eco‐hydrological responses measured at fine scale can overcome these constraints and provide insights into runoff and erosion at scales relevant to management. In this study, runoff and sediment production were modelled on two adjacent hillslopes, one with woody encroachment (3500 stems ha−1) and the other a volunteer pasture cultivated to oats 18 months previously. Spatial modelling was undertaken to integrate small‐plot (1 m2) rainfall simulation, slope and the spatial distribution of ground cover. The estimates of runoff and sediment production in the woody hillslope were considerably lower than in the pasture hillslope in both years of the study. Runoff and sediment production in the woody hillslope were similar in consecutive years, whereas the estimates of runoff and sediment production in the pasture hillslope were lower in the second year as a result of the establishment of a water spreading system of contour banks. The results showed the importance of measuring patchiness and connectivity of runoff source areas for runoff and sediment production. The spatial modelling approach allowed a description of fine‐scale, surface eco‐hydrological interactions on hillslopes, based on high resolution spatial data and experimental fine‐scale rainfall simulations. A similar modelling approach could be used to explore runoff and sediment production resulting from varying management of semi‐arid lands. Copyright © 2011 John Wiley & Sons, Ltd.